2013
DOI: 10.1016/j.vaccine.2012.10.118
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of recombinant Rift Valley fever MP-12 vaccine candidates in sheep

Abstract: The safety and immunogenicity of two authentic recombinant (ar) Rift Valley Fever (RVF) viruses, one with a deletion in the NSs region of the S RNA segment (arMP-12ΔNSs16/198) and the other with a large deletion of the NSm gene in the pre Gn region of the M RNA segment (arMP-12ΔNSm21/384) of the RVF MP-12 vaccine virus were tested in crossbred ewes at 30 – 50 days of gestation. First, we evaluated the neutralizing antibody response, measured by plaque reduction neutralization (PRNT80), and clinical response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
5
55
1
Order By: Relevance
“…MP12, a chemically attenuated virus derived from ZH548, an Egyptian wild-type isolate (Caplen et al 1985, Vialat et al 1997, is being evaluated as a potential vaccine for human and veterinary use. The immunogenicity and pathogenicity of these latter two candidate vaccines have been evaluated in various animal species (Muller et al 1995, Morrill et al 1997, and, although both vaccine candidates showed promising results, MP12 was reported to induce fetal malformations during the first trimester (Hunter et al 2002); however, a recent study reported the absence of fetal malformation in pregnant ewes inoculated with the virus (Morrill et al 2013). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MP12, a chemically attenuated virus derived from ZH548, an Egyptian wild-type isolate (Caplen et al 1985, Vialat et al 1997, is being evaluated as a potential vaccine for human and veterinary use. The immunogenicity and pathogenicity of these latter two candidate vaccines have been evaluated in various animal species (Muller et al 1995, Morrill et al 1997, and, although both vaccine candidates showed promising results, MP12 was reported to induce fetal malformations during the first trimester (Hunter et al 2002); however, a recent study reported the absence of fetal malformation in pregnant ewes inoculated with the virus (Morrill et al 2013). …”
mentioning
confidence: 99%
“…Strategies to develop RVFV vaccines include subunit (Schmaljohn et al 1989, Mandell et al 2010a, DNA (Spik et al 2006), viruslike particles (VLPs) , de Boer et al 2010, Kortekaas et al 2012, virus replicon particles (Kortekaas et al 2011, Dodd et al 2012, Oreshkova et al 2013), virus-vectored (Wallace et al 2006, Heise et al 2009) modified live vaccines, developed from recombinant viruses engineered using reverse genetics (Ikegami et al 2006, Bird et al 2008, Billecocq et al 2008, Habjan et al 2008, Bird et al 2011, live attenuated (Smithburn 1949, Caplen et al 1985, Muller et al 1995, Dungu et al 2010, Pittman 2012, Morrill et al 2013, and inactivated whole virus vaccines (Pittman et al 2000). Although subunit vaccines for RVFV are generally considered safe, and recently some progress has been made in their development, evaluation of immunogenicity and/or efficacy in a target species, sheep, has been performed for a few candidates (Kortekaas et al 2012, Oreshkova et al 2013).…”
mentioning
confidence: 99%
“…126,127,128 In a study of 242 patients exposed to mustard gas during the Iran-Iraq war, Ebadi and colleagues found that, 34 in general, all those suffering sequelae had a lower quality of life, especially with regard to health factors. 126 These researchers also found that sequelae in three or more systems (i.e.…”
Section: Quality Of Lifementioning
confidence: 99%
“…127 Another study found that exposed patients with sequelae suffered chronic and prolonged fatigue, but this differed from clinical definitions of chronic fatigue syndromes. 128 The source of fatigue for the people in this study was often the physical sequelae themselves -for instance, fatigue arising from shortness of breath or muscle weakness caused by mustard-gas exposure. 127 These researchers also found the chronic fatigue of physical origin also caused significant fatigue in some patients.…”
Section: Quality Of Lifementioning
confidence: 99%
“…23 Although these results demonstrate the ability to generate effective DIVA vaccines with increased safety, it was also shown that the immunogenicity of rMP-12-DNSs 16/198 is not as high as the MP-12 vaccine in sheep. 26 A likely explanation for this result is that complete disruption of NSs obviates the virus's ability to counteract the host IFN response and reduces viral replication in vivo. 13 The interesting idea that Ikegami's group next put forward was not to completely disrupt NSs, but "to replace the RVFV NSs with a functional NSs derived from other phleboviruses."…”
mentioning
confidence: 99%